Analysis of the Relationship of Knowledge with the Level of Readiness for Menopause in Premenopause Women in Pisangan Jaya Tangerang 2022 - Devi Liana Eka Sari; Lia Idealistiana (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: menopause is the final stage of the biological processes experienced by women. Hormonal changes during menopause will cause physical and psychological symptoms, with education and knowledge about menopause can encourage ability and readiness aimed especially at premenopausal women. Purpose of this study was to determine and analyze the relationship between knowledge about menopause and the readiness level of premenopausal women. Methods: this type of research is quantitative with a case control research design. The population is premenopausal women aged 40-48 years and residing in Pisangan Jaya Village. The sampling method used was simple random sampling, and the sample in this study was 73 respondents. Collecting data using a questionnaire about knowledge and readiness for menopause. The statistical test used is Chi-square. Results: the results of this study indicate that of the 57 respondents the level of readiness to face menopause is in the ready category, mothers with a good level of knowledge about menopause are in the good category (64.4%), in the sufficient category (13.7%), and in the poor category (0.0%). Of the 16 respondents, mothers with a level of readiness to face menopause were in the unprepared category, mothers with a good level of knowledge about menopause were in the good category (2.7%), in the sufficient category (15.1%), and in the poor category (4.1%). Conclusion: the results of this study also showed that there was a relationship between the level of knowledge of mothers about menopause and the level of readiness to face menopause with a correlation value (p = 0.000). Because the significance value is less than the alpha value (<0.05).